Freedom of expression under Pakistan constitution - Fatiana, Yasir Aleem; Abdul Wahab, Harlida; Halim, Rohizan (Global Academic Excellence, 2018)
Constitution of Pakistan expressly protects freedom of expression. Explicit restrictions are also presented under the constitution. The legislature has enacted several laws based on those restrictions. Laws restricting freedom of expression include Pakistan Penal code 1860, Security of Pakistan Act 1952, Contempt of courts ordinance 2003, Antiterrorism act 1997. This study aims to examine the freedom of expression and restrictions inscribed on it. The doctrinal research method is adopted under this study. The data is collected by constitutional and other legal documents. This study concludes that the laws which regulate freedom of expression have in fact expanded the scope of limitations. This study recommends a comprehensive review of laws related to the regulation of freedom of expression to bring them in harmony with constitutional protection of freedom of expression.